Infinitival complements of causative/perception verbs in a diachronic perspective. - Martins, Ana Maria (2020)
This paper traces the diachrony of three alternative configurations of infinitival complementation with causative and perception verbs in Portuguese, namely the faire-infinitive, the Exceptional Case Marking and the inflected infinitive constructions. It is shown that the faire-infinitive construction is the earlier pattern of infinitival complementation with causative and perception verbs. The ECM construction is the subsequent innovation and creates the conditions for the appearance of the inflected infinitive. Hence the diachronic development of the structures analyzed in the paper defines a clear path of functional enrichment of the infinitival complements of causative and perception verbs, which gradually acquire greater syntactic autonomy. The structurally ambiguous configurations that lie behind each step of the change are identified in the paper.